Grid-integrated and standalone photovoltaic distributed generation systems : analysis, design and control - Zhao, Bo, 1977- (John Wiley & Sons, Inc., 2018)
A practical and systematic elaboration on the analysis, design and control of grid integrated and standalone distributed photovoltaic (PV) generation systems, with Matlab and Simulink models -Analyses control of distribution networks with high penetration of PV systems and standalone microgrids with PV systems -Covers in detail PV accommodation techniques including energy storage, demand side management and PV output power regulation -Features examples of real projects/systems given in OPENDSS codes and/or Matlab and Simulink models -Provides a concise summary of up-to-date research around the word in distributed PV systems.